Improved Synthesis of Symmetrical 2,5-Diarylimidazoles by One-Pot Palladium-Catalyzed Direct Arylation Tailored on the Electronic Features of the Aryl Halide - Lessi, Marco; Panzetta, Gianmarco; Marianetti, Giulia; Bellina, Fabio (Synthesis, 2017)
Two methods for the one-pot synthesis of 2,5-diarylimidazoles by palladium-catalyzed direct C–H arylation of 1-substituted imidazoles with aryl bromides have been devised. The first method, promoted by copper(I) iodide, is best suited for electron-poor aryl bromides, and also allows the 2,5-diarylation of thiazole and oxazole. The use of xylene instead of DMA is the key for the efficiency of the second method, which gives the best results with electron-rich aryl bromides.
Keywords: direct arylation; imidazoles; palladium; C–C coupling; regioselectivity; C–H bond activation; catalysis; aryl halides